Vestibular functions in patients with idiopathic sudden sensorineural hearing loss and its relation to prognosis - Kizkapan, Dondu Betul; Karlidag, Turgut; Basar, Figen; Kaygusuz, Irfan; Keles, Erol; Akyigit, Abdulvahap; Yalcin, Sinasi (Elsevier Sci Ltd, 2022)
Objective: Because of the anatomically close relationship between the cochlea and the vestibular organs, cochlear function disorders may be accompanied by vestibular disorders. This study aimed to evaluate vestibular functions in patients with idiopathic sudden sensorineural hearing loss using VEMP, caloric test, and VNG test battery and its relation to prognosis. Materials and Methods: For this study, 42 patients aged 18-55 years with idiopathic sudden sensorineural hearing loss and 30 volunteers who had no hearing and balance problems were included. Audiometry, cVEMP, oVEMP, caloric tests, and VNG tests were performed. Moreover, the effects of age, sex, time of admission, degree and configuration of hearing loss, accompanying vertigo, tinnitus, and ear fullness on improvement in hearing were evaluated. Results: Of the 42 patients in the study group, 26 (56.52%) were male, 20 (43.48%) were female, and the mean age was 41.54 +/- 12.23 years. Of the 30 individuals in the control group, 19 (63.3%) were male, 11 (36.7%) were female, and the mean age was 39.53 +/- 13.03 years. There was no significant difference in the incidence of sudden sensorineural hearing loss in terms of sex and age, and the prognosis was better for female patients. Early admission to treatment was a factor of good prognosis; profound hearing loss, bilateral hearing loss and vertigo were factors of poor prognosis. Prognosis was better in patients with rising type audiogram configuration, while the prognosis was worse in patients with flat, descending and total hearing loss. Tinnitus and ear fullness had no effect on the prognosis. No anomalies were observed in VNG findings. Moreover, abnormal caloric response was higher in patients with profound hearing loss and total hearing configuration. Shortening was observed in cVEMP / oVEMP P1 and N1 latency after treatment. Furthermore, there was an improvement in abnormal responses after treatment. Conclusion: In this study, vestibular function was affected in patients with idiopathic sudden sensorineural hearing loss. The present study can help the development of a clinical strategy in the evaluation of the vestibular system in idiopathic SSNHL, patient follow-up, patient information, and the implementation of vestibular rehabilitation. Note that additional studies involving larger patients series are required. (C) 2021 Japanese Society of Otorhinolaryngology-Head and Neck Surgery, Inc. Published by Elsevier B.V. All rights reserved.
Keywords: Idiopathic sudden sensorineural hearing loss; Vestibular dysfunction; oVEMP; cVEMP; Caloric test